Pengembangan Strategi Manajemen Sumber Daya yang Efektif untuk Meningkatkan Daya Saing Kewirausahaan Berkelanjutan - Diah Utami; Alfa Firdaus (CV. IRA PUBLISHING, 2026)
In the era of globalization and digitalization, sustainable entrepreneurship is one of the key factors in encouraging inclusive and environmentally friendly economic growth. Effective resource management is a major challenge for business actors, especially in ensuring business competitiveness amidst increasingly fierce competition. Along with technological developments, resource management strategies have also undergone significant transformation. Initially, resource management strategies emphasized operational efficiency and cost savings. However, as awareness of the importance of sustainability increases, this approach has developed into a more holistic strategy that takes into account economic, social and environmental aspects. Indonesian Migrant Workers (TKI) in Penang, Malaysia have a great potential to develop sustainable entrepreneurship. However, many TKI still face difficulties in managing resources effectively, which hinders their entrepreneurship competitiveness. With the advancement of technology and globalization, effective resource management has become crucial to enhance sustainable entrepreneurship competitiveness.